Results of EPRI/ANL DCH investigations and model development - Spencer, B. W.; Sienicki, J. J.; Sehgal, B. R.; Merilo, M. (Argonne National Laboratory, 1988)
The results of a series of five experiments are described addressing the severity and mitigation of direct containment heating. The tests were performed in a 1:30 linear scale mockup of the Zion PWR containment system using a reactor-material corium melt consisting of 60% UO/sub 2/, 16% ZrO/sub 2/, 24% SSt at nominally 2800C initial temperature. A ''worst-case'' type test involving unimpeded corium dispersal through an air atmosphere in a closed vessel produced an atmosphere heatup of 323K, equivalent to a DCH efficiency of 62%. With the addition of structural features which impeded the corium dispersal, representative of dispersal pathway features at Zion, the DCH efficiency was reduced to 1--5%. (This important result is scale dependent and requires larger scale tests such as the SURTSEY program at SNL plus mechanistic modeling for application to the reactor system.) With the addition of water in the cavity region, there was no measurable heatup of the atmosphere. This was attributable to the vigorous codispersal of water with corium which prevented the temperature of the atmosphere from significantly exceeding T/sub sat/. In this case the DCH load was replaced by the more benign ''steam spike'' from corium quench. Significant oxidation of the corium constituents occurred in the tests, adding chemical energy to the system and producing hydrogen. Overall, the results suggest that with consideration of realistic, plant specific, mitigating features, DCH may be no worse and possibly far less severe than the previously examined steam spike. Implications for accident management are addressed. 17 refs., 7 figs., 4 tabs.